Implementasi Kebiajakan Pimpinan dalam Sistem Pengendalian Manajemen Islam terhadap Kinerja di Perusahaan/ Organisasi - Ria Anjriani Sahputri; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
The Big Indonesian Dictionary defines implementation as generally meaning implementation or implementation. Typically, an action taken to accomplish a certain aim is referred to as implementation. Implementation is one of the efforts to be made in a system.The policy has been determined, because without implementing a concept it will never materialize, right? Implementation of true wisdom, The act of influencing people to comprehend and concur on what must be done and how to execute it, as well as the act of assisting both individual and group efforts to reach shared objectives, is known as leadership. Management is the act of creating and sustaining an environment where people may successfully accomplish the desired outcome by cooperating in groups. Expanding on this fundamental concept, managers are those who carry out the managerial duties of staffing, organizing, planning, leading, and controlling.Management makes human endeavors more productive. It brings better equipment, factories, offices, products, services and human relations to our society, Management control is not automatic. For example, when there is an accumulation of patients, there is not a single tool that is able to handle this automatically, but information from the detector, assessment from the assessor and changes by the effector are needed. The ability to govern management involves cooperation amongst people. Each component must cooperate with the others, and management control must guarantee this.